Case Report: Staged bilateral pancarpal arthrodesis using 3D-printed patient specific guides and customized hybrid plate for severe carpal joint instability associated with chronic inflammatory demyelinating polyneuropathy in a miniature dachshund - Franca, Adriana; Marco-Carpio, Isabel; Oxley, Bill; Mínguez, Juan J.; Vallefuoco, Rosario (Frontiers in Veterinary Science, 2025)
This clinical case report aims to describe the surgical treatment of a severe bilateral multilevel and multidirectional carpal joint instability associated with chronic inflammatory demyelinating polyneuropathy (CIDP) with staged bilateral pancarpal arthrodesis (PCA) using 3D-printed patient specific guides and customized hybrid plate in a nine-year-old female neutered Dachshund. The dog was presented due to a progressive acute onset of generalized weakness. Neurological examination, blood work, electromyography, muscle, nerve biopsies and treatment responsiveness led to a diagnosis of CIDP. Medical treatment of the CIDP resulted in resolution of muscle weakness, but did not improved the carpal hyperextension, that ultimately ended up in a severe joint instability, requiring bilateral PCA. Staged bilateral PCA using 3D-printed patient specific guides and customized hybrid plate successfully treated the carpal joint instability without associated complications and resulted in a good to excellent return to function and quality of life of the patient. PCA in chondrodystrophic and miniature breeds can be challenging. Using 3D-printed patient specific guides and customized hybrid plate in this case helped in reducing the surgical time, and offering a more stable construct.